Value-Based Pricing in Malaysia's Healthcare: A stakeholder analysis - Amirul Ashraf; Siew Chin Chin Ong (ACHSM, 2022)
Background: High pharmaceutical price is a dilemma. Value-based pricing (VBP) is suggested to be the potential solution to this problem. However, in Malaysia, VBP does not receive favorable response from the industry players. Therefore, in this study we would like to examine the position of various stakeholders on this issue. Methods: The PolicyMaker tool is used to evaluate the position and interest of the various stakeholders. Next, we assess the factors that might contribute to the policy success or failure using Kingdon's multiple stream approach Results: We found that VBP received positive response from the stakeholders with some request for amendments. There was unanimity among the stakeholders about introducing medications that do not improve patient outcomes is counterproductive, therefore the problem has been articulated adequately. The policy was sufficiently explained with the publication of the guidelines. Continuous engagement between the government and the private sector plays a major role. Strong political will also contributed to the success. Conclusion: Our findings showed that VBP implementation is successful due to strategic engagement and strong support from the government and the private sectors.